Characteristics of Viscoelastic-Surfactant-Induced Wettability Alteration in Porous Media - Kexing Li; Bowen Chen; Wanfen Pu; Xueqi Jing; Chengdong Yuan; Mikhail Varfolomeev (Energies, 2021)
Wettability alteration is one of the most important mechanisms of surfactant flooding. In this work, the combined Amott/USBM (United States Bureau of Mines) method was applied to study the average wettability alteration of initially neutral cores after viscoelastic-surfactant (VES) filtration. The effects of static aging, dynamic aging, VES concentration, filtration flow rate, and pore radius on the alteration of a core’s average wettability were studied. The wettability-alteration trends measured by Amott and USBM were consistent, demonstrating that the overall hydrophilicity of the core was enhanced after VES filtration. The wettability alterations of the core brought about by dynamic aging were more significant than by static aging. The viscoelastic properties of the VES played an important role in altering the wettability. In addition, the ability of the VES to affect the core’s wettability was significantly enhanced when the VES concentration was increased, which was beneficial in increasing VES adsorption on the pore-wall surface, thus altering the overall wettability of the core. Increasing filtration flow rates can destroy those high-viscosity VES aggregates via the higher shear rate. A higher retention of VES makes the core more hydrophilic. The difference in the wettability of cores with different pore radius after VES filtration was not significant. The alteration of average wettability caused by VES in porous media provides a new vision for studying the EOR mechanism of VES.